Resistance and conformity in the Third Reich - Housden, Martyn, 1962- (Routledge sources in history., 1997)
This is a thematically arranged text illustrating popular resisitance to Nazism in Germany from 1930-1945, and the affect of Nazism on everyday life. The book combines a lucid, synthesized analysis together with a wide selection of integrated source material taken from pamphlets, diaries, recent oral testimonies, correspondence and more. Different chapters focus on social groups and activities, such as youth movements, religion, Jewish Germans, and the working classes.